Labour market and collective bargaining in Iceland: sharing the spoils without spoiling the shares - Sila, Urban (OECD Economics Department Working Papers, 2017)
Iceland has high living standards, low poverty, high inclusiveness and one of the most sustainable pension systems. It is the most highly unionised country in the OECD and, in the past, successful social pacts have protected the lowest paid workers during crises, and on occasion helped fight inflation. Nevertheless, Iceland experiences recurrent bursts of social tensions and labour unrest that often result in large wage awards, particularly in times of economic boom. Iceland is prone to accentuated economic cycles, and the pro-cyclical nature of collective bargaining aggravates these harmful dynamics. Social partners often have disagreements over what has been agreed in the past and they can have differing views on the state of the economy. Trust among the social partners has been undermined and wage co-ordination is low. There is a large number of unions, many of them very small, and wage demands are often not consistent with macroeconomic stability. Labour unrest frequently originates in the public sector as wages lag behind the private sector. Fostering trust and increasing wage co-ordination would make collective bargaining more effective and help sustain the benefits of the system for future generations. A technical committee should be established to provide reliable and impartial information to wage negotiators. Wage negotiations could start with "wage guidelines" issued by the major labour and employer confederations. State mediator should have greater powers in order to improve wage co-ordination and support the "wage guidelines". This working paper relates to the 2017 OECD Economic Survey of Iceland (http://www.oecd.org/eco/surveys/economic-survey-iceland.htm)